A reply to Mayers and Rice (1979) - Roll, Richard (Journal of Financial Economics, 1979)
Mayers and Rice do not resolve the basic problem in portfolio performance evaluation with the securities market line, the ambiguity introduced by being obliged to choose a market index. Other performance evaluation techniques exist and possess some superior qualities. The Mayers-Rice discussion of my critique of the capital asset pricing model (CAPM) fails to recognize the CAPM's unusual testing implications and ignores the existence of alternative asset pricing theories. Residual analysis should give approximately correct estimates of the abnormal returns caused by specific events if it is conducted with the market model.